THE ACCOUNTING PRACTICE OF BUWUHAN TO FOSTER SOCIAL LIVES THROUGH THE VALUE RUKUN AGAWE SANTOSA, CRAH AGAWE BUBRAH - Ramadhania, Reza (Institut Teknologi dan Bisnis Asia Malang, 2024)
This research aims to explore the practice of buwuhan accounting in enhancing the value of community life. To comprehend reality comprehensively and thoroughly, the research employs a postmodernist paradigm. Data collection for the research was obtained through interviews with informants and articles published in journals. The data analysis technique employs the Javanese proverb rukun agawe santosa, crah agawe bubrah, which translates to harmony strengthens, conflict disrupts. This proverb embodies the values of harmony, cooperation, peace, dishonesty, and conflict. The research findings reveal that the practice of buwuhan accounting contributes to harmony and reduces conflicts through asset acceptance, expense management, cash flow recording, and debt acknowledgment in the buwuhan tradition. Through buwuhan accounting practices, harmony can be maintained, and disputes reduced, when conducted with a sense of unity, cooperation, and peace.